A Randomized, Placebo-Controlled Phase 2 Trial of CNTO 6785 in Chronic Obstructive Pulmonary Disease - Eich, Andreas; Urban, Veronika; Jutel, Marek; Vlcek, Jiri; Shim, Jae Jeong; Trofimov, Vasiliy I.; Liam, Chong-Kin; Kuo, Ping-Hung; Hou, Yanyan; Xiao, Jun; Branigan, Patrick; O'Brien, Christopher D. (Chronic obstructive pulmonary disease, 2017)
Interleukin (IL)-17A may be an underlying factor in the pathophysiology of chronic obstructive pulmonary disease (COPD). Anti-IL-17 monoclonal antibodies have been used successfully in treating several immune-mediated inflammatory diseases. This phase 2, randomized, placebo-controlled, double-blind, parallel-group, proof-of-concept study is the first clinical study evaluating the efficacy and safety of the anti-IL-17A monoclonal antibody CNTO 6785 in patients with symptomatic moderate-to-severe COPD. Patients were treated with CNTO 6785 (n = 93) or placebo (n = 94) intravenously at Weeks 0, 2, and 4 (induction), then Weeks 8 and 12, and followed till Week 24. The primary efficacy endpoint was the change from baseline in pre-bronchodilator percent-predicted forced expiratory volume in 1 second at Week 16. Samples were collected at all visits for pharmacokinetic (PK) evaluation, and standard safety assessments were performed. The mean difference in the primary efficacy endpoint between CNTO 6785 and placebo was not statistically significant (−0.49%; p = 0.599). No other efficacy endpoints demonstrated clinically or statistically significant differences with CNTO 6785 compared with placebo. CNTO 6785 was generally well tolerated; no major safety signals were detected. The most frequently reported treatment-emergent adverse events were infections and infestations; however, no notable differences were observed between CNTO 6785 and placebo in terms of rates of infections. PK results suggested that the steady state of serum CNTO 6785 concentration was reached within 16 weeks. These results suggest that IL-17A is unlikely to be a dominant driver in the pathology of, or a viable therapeutic target for, COPD. ClinicalTrials.gov Identifier: NCT01966549; EudraCT Identifier: 2012-003607-36.